No useless labour: Oscar Wilde's De Profundis and the importance of intellectual work*. Issue 6 (3rd July 2019) - Gerzso, Christian
ABSTRACT: This article argues that Oscar Wilde significantly reassesses his aesthetic theory in De Profundis, in particular, his concept of intellectual labour. By focusing on his account of the challenges of reading and writing in prison, this article demonstrates how Wilde begins to theorise intellectual activity as a kind of work and, in the process, redefines his aestheticism in order to include notions of physical effort. Wilde writes De Profundis in direct response to the English prison system of the 1890s, which forced inmates to perform punitive labour as a way to inflict on them a sense of futility. For this reason, Wilde reconsiders his polemical defences of art making and criticism as idle, and instead, conceives of intellectual work as a free and productive activity: in contrast to the uselessness of prison labour, Wilde sees himself producing something of aesthetic value by writing his text. Thus, De Profundis signals an important shift in his thought: it moves away from Wilde's earlier celebrations of dandy indolence and emphasises instead the work entailed in writing. In this way, De Profundis puts forth a critique not only of alienated labour, as Wilde had done before his imprisonment, but also of alienated leisure.